Anterior cruciate ligament injuries in professional hockey players - Sikka, R.; Kurtenbach, C.; Steubs, J. T.; Boyd, J. L.; Nelson, B. J. (The American Journal of Sports Medicine, 2016)
Background: Performance outcomes and return-to-play data have been reported after anterior cruciate ligament (ACL) injuries in professional football and basketball, but they have rarely been reported in professional hockey.